Validity and reliability of wearable devices during self-paced walking, jogging and overground skipping - Navalta, J. W.; Davis, D. W.; Carrier, B.; Malek, E. M.; Vargas, N.; Rodriguez, J. P.; Weyers, B.; Carlos, K.; Peck, M. (SportMont, 2023)
Wearable technology can track unusual exercise, providing data for improving fitness. The aim of the study was to determine validity and reliability during walking, jogging, and skipping. Eighteen volunteers completed 5 min self-paced activities interspersed with 5 min rest. Variables and devices were step count (Garmin Instinct), estimated energy expenditure (Garmin Instinct, Polar Vantage M2), and heart rate (Garmin Instinct, Polar Vantage M2, Polar OH1, Polar Verity Sense). Validity measures were mean absolute percent error (MAPE) and Lin`s Concordance (CCC), and reliability were coefficient of variation (CV), and intraclass correlation (ICC). Thresholds were MAPE =5%, CCC=0.90, CV=10%, ICC=0.70. Garmin Instinct step count during skipping was not considered valid (MAPE=90.2%, CCC=0.008) or reliable (CV=6%, ICC CI=0.4). Energy expenditure during skipping was not valid or reliable in the Garmin Instinct (MAPE=28%, CCC=0.27; CV=19%, ICC=0.61) or the Polar Vantage M2 (MAPE=19%, CCC=0.57; CV=13%). While the Polar Vantage M2 was reliable for estimated energy expenditure during walking and jogging activities, wrist-worn devices (Garmin Instinct, Polar Vantage M2) were neither valid nor reliable in returning estimated energy expenditure during overground skipping. From a wider perspective, wearable device algorithms for estimating energy expenditure should continue to be refined until they return the same level of accuracy as what is currently observed for heart rate, and to a lesser extent step count. Skipping may be an excellent unusual activity for testing wearable devices.